2006
DOI: 10.1073/pnas.0601289103
|View full text |Cite
|
Sign up to set email alerts
|

A functional AMPA receptor–calcium channel complex in the postsynaptic membrane

Abstract: Ca 2؉ channels play critical roles in the regulation of synaptic activity. In contrast to the well established function of voltageactivated Ca 2؉ channels in the presynaptic membrane for neurotransmitter release, some studies are just beginning to elucidate the functions of the Ca 2؉ channels in the postsynaptic membrane.In this study, we demonstrated the functional association of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptors with the neuronal Ca 2؉ channels. A series of biochemical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The γ 2 calcium channel subunit 'stargazin' has been likened to an auxillary subunit of the AMPAR and is importantly involved in AMPAR trafficking and function (Tomita et al, 2005;Vandenberghe et al, 2005;Tomita et al, 2006). More recently, neuronal calcium channels have been shown to reside in a multimolecular complex including the GluR1 and GluR2/3 AMPA receptor subunits which, in turn, co-immunoprecipitate with the pore forming α1 subunit CAv2.1 (Kang et al, 2006). These findings point to the speculative possibility that integrin signaling may regulate AMPAR coupling with calcium channel proteins (γ 2 , CAv2.2, and maybe others) and thereby strengthen the influence of these glutamate receptors over calcium channel gating.…”
Section: Discussionmentioning
confidence: 99%
“…The γ 2 calcium channel subunit 'stargazin' has been likened to an auxillary subunit of the AMPAR and is importantly involved in AMPAR trafficking and function (Tomita et al, 2005;Vandenberghe et al, 2005;Tomita et al, 2006). More recently, neuronal calcium channels have been shown to reside in a multimolecular complex including the GluR1 and GluR2/3 AMPA receptor subunits which, in turn, co-immunoprecipitate with the pore forming α1 subunit CAv2.1 (Kang et al, 2006). These findings point to the speculative possibility that integrin signaling may regulate AMPAR coupling with calcium channel proteins (γ 2 , CAv2.2, and maybe others) and thereby strengthen the influence of these glutamate receptors over calcium channel gating.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemistry of Native Neuronal VDCC Complexes-To obtain the crude synaptic membrane (CSM) fraction, subcellular fractionation was performed based on a previously described method (24), with slight modification. Whole mouse brains (8 g) were homogenized in a homogenization buffer containing 4 mM HEPES, 0.32 M sucrose, 5 mM EDTA, 5 mM EGTA, and protease inhibitors (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…21 A recent study demonstrated the physical and functional association of AMPA receptors and voltagegated Ca 2+ channels in a complex with scaffolding proteins in brain tissue. 19 As prior studies have demonstrated predominantly GluR2-containing AMPA receptors in the DMNV, which are generally Ca 2+ -impermeable and undergo rapid desensitization, the results of the present study suggest a functional association between AMPA receptors and T-type Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 57%
“…Because most AMPA receptors are Ca 2+ -impermeable, and a functional association has been shown to voltagegated Ca 2+ channels 18,19 , the next series of experiments sought to determine if any subtype of Ca 2+ channels may be involved. The three major subtypes are T-type, L-type, and N-type Ca 2+ channels.…”
Section: Resultsmentioning
confidence: 99%